2014
DOI: 10.1002/ejp.564
|View full text |Cite
|
Sign up to set email alerts
|

More ubiquitous effects from non‐pharmacologic than from pharmacologic treatments for fibromyalgia syndrome: A meta‐analysis examining six core symptoms

Abstract: This study aimed to characterize and compare the efficacy profile on six fibromyalgia syndrome (FM) core symptoms associated with pharmacologic and non-pharmacologic treatments. We screened PubMed, Embase and the Cochrane Library for FM articles from 1990 to September 2012 to analyse randomized controlled trials comparing pharmacologic or nonpharmacologic treatments to placebo or sham. Papers including assessments of at least 2 of the 6 main FM symptom domains -pain, sleep disturbance, fatigue, affective sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 104 publications
1
58
0
3
Order By: Relevance
“…A single systematic review of two studies involving 74 patients reported an effect size on pain of 1.36 (0.01 to 1.34) 16. The improvement in functional deficit was not statistically significant (1.24; −0.36 to 2.84).…”
Section: Resultsmentioning
confidence: 99%
“…A single systematic review of two studies involving 74 patients reported an effect size on pain of 1.36 (0.01 to 1.34) 16. The improvement in functional deficit was not statistically significant (1.24; −0.36 to 2.84).…”
Section: Resultsmentioning
confidence: 99%
“…It should also include some form of aerobic exercise, which is quite consistently shown to improve pain and generally results in larger effect sizes than pharmacotherapy at least on global well being and physical function and affects more different domains [582]. The best type of exercise, particularly whether it should be land-based or water-based, has not been firmly established [583].…”
Section: Treatment and Outcome Treatmentmentioning
confidence: 98%
“…• • effect of current treatment for fibromyalgia on sleep A recent systematic review and meta-analysis examined the effect of current nonpharmacological and pharmacological treatment on different core symptoms of fibromyalgia [54]. Studies on nonpharmacological treatments often combined several treatments.…”
Section: • • Disturbed Sleep Impairs Pain Processingmentioning
confidence: 99%